PEMANFAATAN LAMPU LED BOLHAM EMERGENCY DAN LIMBAH KAYU KONSTRUKSI UNTUK PENERANGAN POS KAMPLING DESA PUCANGRO - Annisa' Carina; Khoirotun Ni'mah (Universitas Mataram, 2023)
The village of Pucangro is already electrified by PLN, especially the residents' houses, most of which already have a power source. However, there are several points that require routine maintenance, such as village posts or posts. It is undeniable that the Basic Electricity Tariff (TDL) is quite a burden on the human economy. It can therefore be replaced with an emergency LED light bulb. While the placement of the lights is made by utilizing wood construction waste. Wood waste is processed into goods or furniture that have a sale value. Therefore, this community service activity is important to do because it provides knowledge that emergency LED lights can be used as a solution to save electricity, and wood waste from construction can be reprocessed into items or furniture that have a sale value.